Direction to practical production of hydrogen by formic acid dehydrogenation with Cp*Ir complexes bearing imidazoline ligands. Issue 4 (24th November 2015) - Onishi, Naoya; Ertem, Mehmed Z.; Xu, Shaoan; Tsurusaki, Akihiro; Manaka, Yuichi; Muckerman, James T.; Fujita, Etsuko; Himeda, Yuichiro
Abstract : A Cp*Ir complex with pyridyl-imidazoline achieved the quantity production of 1 m 3 of H2 /CO2 gases from only HCO2 H in water without any additives. Abstract : A Cp*Ir complex with a bidentate pyridyl-imidazoline ligand achieved the evolution of 1.02 m 3 of H2 /CO2 gases by formic acid dehydrogenation without any additives or adjustments in the solution system. The pyridyl-imidazoline moieties provided the optimum pH to be 1.7, resulting in high activity and stability even at very acidic conditions.